Kualitas hidup wanita menopause di perkotaan: peran karakteristik sosiodemografi - sri winarsih; Siti Chunaeni; Nuril Nikmawati; Wiji Lestari (Midwifery and Nursing Research, 2026)
Background: Menopause is a natural biological transition characterized by the permanent cessation of menstruation due to decreased ovarian production of estrogen and progesterone. These hormonal changes may lead to physical and psychological symptoms that potentially affect women’s quality of life. Assessing quality of life among menopausal women is essential to identify their health status and well-being, particularly in urban settings where lifestyle factors may influence adaptation to menopause. Objective: This study aimed to examine the association between sociodemographic characteristics and the quality of life of menopausal women in urban areas. Methods: An analytic correlational study with a cross-sectional design was conducted among 49 menopausal women selected through total sampling. Quality of life was measured using the WHOQOL-BREF instrument, covering physical health, psychological health, social relationships, and environmental domains. Bivariate analysis was performed using the Chi-square test with a significance level of 5%. Results: Most respondents were postmenopausal, had primary–secondary education, were employed, and were married. The majority reported moderate quality of life in the physical domain and good quality of life in the psychological, social, and environmental domains. Age was significantly associated with quality of life in the physical and social domains (p < 0.05). No significant associations were found between education level, employment status, or marital status and quality of life (p > 0.05). Conclusion: Age significantly influences quality of life among menopausal women, particularly in physical and social aspects. Strengthened health promotion and family support are recommended to improve well-being during menopause. Keywords: menopause; characteristics; quality of life; menopausal women. 1,2,3 Midwifery Study Program in Magelang Department of Midwifery, Health Polytechnic of Semarang, Indonesia Jl. Perintis Kemerdekaan Magelang, Jawa Tengah, Indonesia 4 Community Health Centers of Kerkopan, Magelang city.